Time-Kill Kinetics of Lipid Fractions Isolated from Condiments against Foodborne Pathogens - Ayeza Naeem; Tanveer Abbas; Tahira Mohsin Ali; Abid Hasnain (Food Technology and Biotechnology, 2018)
Lipid fractions that are extracted from condiments have a wide array of biological potential and are commonly utilized for medicinal and culinary applications. This investigation aims at determining the antimicrobial potential of lipid fractions isolated using two different solvent systems against five foodborne pathogens. The antibacterial efficacy was tested after 0, 1, 2, 3 and 24 h of incubation with the active agent. The leakage of cellular content was assessed at 1 and 2 h of incubation. Scanning electron microscope (SEM) images were obtained after 18 h of contact time with lipid fractions at their minimum inhibitory concentration (MIC). From the results obtained from time-kill and cell constituents release tests, it could be concluded that during 3 and 1 h of incubation, the lipid fractions were more potent against Gram-negative isolates (Escherichia coli ATCC 8739). However, prolonged incubation with the active agent inhibited Gram-positive isolate, i.e. Listeria monocytogenes ATCC 13932. SEM images of treated microorganisms also confirmed the inhibitory action of selected lipid fractions against all the tested pathogens. The cellular morphology of the bacteria was completely altered after 18 h of incubation with the lipid fractions. The results of the present study corroborate significant inhibitory effects and disruption in bacterial cell integrity following prolonged incubation with these lipid fractions. The results also affirm the use of the tested lipid fractions in food systems.